Geologia, arte e paesaggi: un report dal GIT 2009 - Santarsiero, Domenico (GEOmedia, 2009)
Geology, art and landscapes: welcome to GIT 2009 GIT (Geology and Information Technology) is a unique event with an alternative format (with a union of geological-technological- wine-food-art union!) and approach to the themes related to geology and its applications. The 2009 editionhas been held in Cagli, a small historic town in the italian Marche region.